Wakaf Syariah Sebagai Instrumen Pendidikan Jangka Panjang - Khoirinisa, Nita; Hadiowati Putri, Noor Vita; Fatikhatur Riziqiyah, Metiya (Universitas Muhammadiyah Surabaya, 2026)
Long-term education financing remains a structural challenge in the development of human resources in Indonesia, along with increasing educational funding needs and limited conventional financial sources. In this context, Islamic waqf has the potential to serve as an alternative and sustainable instrument for education financing. This study aims to analyze the role of Islamic waqf particularly productive waqf and cash waqf as well as waqf governance in supporting long-term education financing in Indonesia. The study employs a qualitative approach using a literature review method by examining scholarly journal articles, academic books, waqf institutional reports, and relevant regulations. Data were analyzed using descriptive qualitative analysis to examine the concepts, mechanisms, and challenges of waqf management in the education sector. The findings indicate that Islamic waqf has significant potential to strengthen education financing through productive and sustainable management of waqf assets. However, the optimization of waqf remains constrained by governance limitations, nazhir managerial capacity, and low waqf literacy. Therefore, strengthening waqf governance and developing innovative productive waqf instruments are key to positioning Islamic waqf as an inclusive and equitable source of long-term education financing.